2019
DOI: 10.1002/admi.201901747
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Native Block Copolymer Thin Film Nanostructures Derived from Iterative Self‐Assembly Processes

Abstract: Nanostructured block copolymer (BCP) thin films constitute an elegant tool to generate complex periodic patterns with periodicities ranging from a few nanometers to hundreds of nanometers. Such well‐organized nanostructures are foreseen to enable next‐generation nanofabrication research with potent applications in the design of functional materials in biology, optics or microelectronics. This valuable platform is, however, limited by the geometric features attainable from diblock copolymer architectures consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 121 publications
(185 reference statements)
0
18
0
Order By: Relevance
“…Another novel concept for the design of complex 3D nanostructures is based on a layering process derived from the iterative self-assembly of BCP layers. [287] Controlled multilayered structures are known as ideal candidates for the design of complex flat optics with a wide variety of functionalities. [288] Pioneering work by Rahman et al [289] demonstrated the potential application of multilayer BCP self-assembly to produce a large library of 3D structures that are absent in the native BCP phase diagram, including sphere-on-line or line-on-line configurations (see Figure 14B).…”
Section: Bcp and Metamaterials Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another novel concept for the design of complex 3D nanostructures is based on a layering process derived from the iterative self-assembly of BCP layers. [287] Controlled multilayered structures are known as ideal candidates for the design of complex flat optics with a wide variety of functionalities. [288] Pioneering work by Rahman et al [289] demonstrated the potential application of multilayer BCP self-assembly to produce a large library of 3D structures that are absent in the native BCP phase diagram, including sphere-on-line or line-on-line configurations (see Figure 14B).…”
Section: Bcp and Metamaterials Future Directionsmentioning
confidence: 99%
“…Another novel concept for the design of complex 3D nanostructures is based on a layering process derived from the iterative self‐assembly of BCP layers. [ 287 ] Controlled multilayered structures are known as ideal candidates for the design of complex flat optics with a wide variety of functionalities. [ 288 ] Pioneering work by Rahman et al.…”
Section: D Gyroid Metamaterialsmentioning
confidence: 99%
“…In their review, Demazy et al present an overview of novel iterative block copolymer self‐assembly processes stacking different block copolymer layers for the generation of “non‐native” morphologies beyond the classical bulk equilibrium phase diagram. [ 17 ] They highlight the great progress in the design of multilayered hierarchical structures enabled by both the understanding of the mechanisms controlling self‐assembly in block copolymer thin film and the development of hybridization methods for the immobilization of the block copolymer pattern and deposition of an additional block copolymer film. At the same time they identify several challenges, such as those related to the implementation of suitable protocols for the precise registration of the block copolymer features and to the understanding of defect annihilation mechanisms in the formation of such structures.…”
Section: Figurementioning
confidence: 99%
“…14,15 To extend the versatility of BCP structures further, several other groups who study BCPs have suggested innovative BCPmanipulating methods to generate a variety of complex and unique 3D nanostructures. [16][17][18][19][20] In particular, Tavakkoli et al demonstrated how to obtain bi-layered 3D BCP morphologies by using a post array for which the surface was modified with a brush attractive to the majority block of di-BCP. 21 They showed a rich variety of 3D nanostructures consisting of line structures with controllable angles, bends, and junctions by adjusting the height and chemical preferences of nano-post templates.…”
Section: Introductionmentioning
confidence: 99%